n Ondersoek na die digitale dataverwerking by flikkergrafie - Lotter, M. G.(Mattheus Gerhardus) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (Ph.D.(Geneesk. Wet.)) -- Universiteit van Stellenbosch,, 1972.